Substantial bulk photovoltaic effect enhancement via nanolayering - Fenggong Wang (Nature Portfolio, 2016)
Spontaneous polarization in ferroelectric materials leads to their use as photovoltaic devices. Here, the authors show by first-principles calculations how nanolayering of PbTiO3with nickel ions and oxygen vacancies can result in enhanced photocurrents due to smaller bandgaps and photocurrent alignment.